Searching for sharp drops in the incidence of pandemic A/H1N1 Influenza by single year of age - Hartman Jacobs, Jessica (2012)
Fil: Hartman Jacobs, Jessica. Harvard School of Public Health. Department of Epidemiology; Estados Unidos.